2003
DOI: 10.1038/nature01707
|View full text |Cite
|
Sign up to set email alerts
|

The cytidine deaminase CEM15 induces hypermutation in newly synthesized HIV-1 DNA

Abstract: High mutation frequency during reverse transcription has a principal role in the genetic variation of primate lentiviral populations. It is the main driving force for the generation of drug resistance and the escape from immune surveillance. G to A hypermutation is one of the characteristics of primate lentiviruses, as well as other retroviruses, during replication in vivo and in cell culture 1-6 . The molecular mechanisms of this process, however, remain to be clarified. Here, we demonstrate that CEM15 (also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
887
6
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 963 publications
(918 citation statements)
references
References 30 publications
23
887
6
2
Order By: Relevance
“…To detect edited elements, we assumed that a newly edited element should be almost identical to its ancestral element except for a few dense clusters of G-to-A mismatches, as such clusters are the hallmark of APOBEC3 editing [10][11][12][13] . To confirm that the mismatches are due to DNA editing, we exploited the asymmetry, or strand specificity, of editing: as opposed to random mutagenesis, APOBEC3 generates C-to-U mutations specifically on the negative strand of the element (with respect to the ORF), yielding clusters of G-to-A mutations, but not C-to-T, on the positive strand [10][11][12] .…”
Section: Identification Of Editing Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…To detect edited elements, we assumed that a newly edited element should be almost identical to its ancestral element except for a few dense clusters of G-to-A mismatches, as such clusters are the hallmark of APOBEC3 editing [10][11][12][13] . To confirm that the mismatches are due to DNA editing, we exploited the asymmetry, or strand specificity, of editing: as opposed to random mutagenesis, APOBEC3 generates C-to-U mutations specifically on the negative strand of the element (with respect to the ORF), yielding clusters of G-to-A mutations, but not C-to-T, on the positive strand [10][11][12] .…”
Section: Identification Of Editing Sitesmentioning
confidence: 99%
“…To confirm that the mismatches are due to DNA editing, we exploited the asymmetry, or strand specificity, of editing: as opposed to random mutagenesis, APOBEC3 generates C-to-U mutations specifically on the negative strand of the element (with respect to the ORF), yielding clusters of G-to-A mutations, but not C-to-T, on the positive strand [10][11][12] . We therefore aligned, pairwise, the positive strands of all retrotransposons from selected families, and scanned the alignments for windows containing a particularly large number of G-to-A mismatches but no mismatches of any other type (Fig.…”
Section: Identification Of Editing Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lethal mutagenesis through deamination of RNA/DNA by cytidine deaminases has been proven to work as an antiviral mechanism against retroviruses 1619, 2327 , and some DNA 2831 and RNA 32 viruses infecting mammals. Our results show that the A. thaliana CDA1 gene has some degree of mutagenic activity on the pararetrovirus CaMV genome.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular nature of permissivity and the exact function of Vif in infection of nonpermissive cells was not known until recently when a series of reports showed that a host cellular protein known as APOBEC3G (apolipoprotein B mRNA-editing enzyme catalytic polypeptide-like 3G) is a potent inhibitor of HIV infection in the nonpermissive cells [70,71]. APOBEC3G is a member of the cytidine deaminase family, which prevents viral cDNA synthesis via deaminating deoxycytidines (dC) in the minus-strand retroviral cDNA replication intermediate [72][73][74][75][76]. As a result, it creates stop codons or G-A transitions in the newly synthesized viral cDNA which is then subjective to elimination by host DNA repair machinery [74,76].…”
Section: Virus Infectivity Factor (Vif)mentioning
confidence: 99%